The Effect of Self-assessment on the Development of EFL Writing Self-Efficacy: A Case of Algerian Higher Education - Kenza Takarroucht (International Journal of Language Education, 2022)
Using self-assessment as part of writing courses is key to improving strategic and affective self-regulation skills. The aim of this study is to investigate how self-assessment develops EFL students’ writing self-efficacy. To conduct this research, an embedded mixed-methods design was implemented with a sample of sixty control and experimental participants. This involved a post-scale of writing self-efficacy to collect quantitative data, and an interview administered to twenty participants after the experiment to explore their perceptions of their writing ability. Data were analysed using descriptive statistics and an independent-samples t-test at α=0.05.  Analysis of the data revealed that the mean score of the experimental group was higher than that of the control group on the self-efficacy scale, and the difference between the two groups was statistically significant on the same variable. Data from the interview indicated that the majority of the participants voiced high perceptions of paragraph writing ability. Based on these findings, it can be assumed that self-assessment is a learning strategy which can enhance learners’ knowledge of criteria of good work and thus, can improve positive perceptions of their writing ability.  This means that self-assessment can maximize their self-efficacy beliefs. Based on these findings, the study suggests recommendations for teachers to include self-assessment in their writing courses.